2015
DOI: 10.1007/s11302-015-9460-9
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity is species-dependent: Characterization of standard agonists and antagonists at human, rat, and mouse adenosine receptors

Abstract: Adenosine receptors (ARs) have emerged as new drug targets. The majority of data on affinity/potency and selectivity of AR ligands described in the literature has been obtained for the human species. However, preclinical studies are mostly performed in mouse or rat, and standard AR agonists and antagonists are frequently used for studies in rodents without knowing their selectivity in the investigated species. In the present study, we selected a set of frequently used standard AR ligands, 8 agonists and 16 ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
148
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(157 citation statements)
references
References 79 publications
5
148
3
Order By: Relevance
“…As shown in Figure 2a, the antiproliferative effect of adenosine was primarily mediated by A 2B AR, because it was abrogated by MRS. The opposing effects of the nonselective agonist NECA and the endogenous ligand adenosine are probably due to the higher affinity of NECA for the A 2A AR (see Supplementary Table S1) (Alnouri et al, 2015), thus explaining the previously reported divergences regarding the effect of AR activation on NHEK proliferation.…”
Section: Resultsmentioning
confidence: 93%
“…As shown in Figure 2a, the antiproliferative effect of adenosine was primarily mediated by A 2B AR, because it was abrogated by MRS. The opposing effects of the nonselective agonist NECA and the endogenous ligand adenosine are probably due to the higher affinity of NECA for the A 2A AR (see Supplementary Table S1) (Alnouri et al, 2015), thus explaining the previously reported divergences regarding the effect of AR activation on NHEK proliferation.…”
Section: Resultsmentioning
confidence: 93%
“…Notably, preischemic exposure to a selective A1R agonist (CCPA) essentially mimicked preconditioning in the liver through a mitochondrial adaptation similar to ischemic preconditioning. The single used dose of CCPA is expected to engage A1R since CCPA is 32 times selective for A1R versus A3 receptors in rats [61]. The possible involvement of A3 receptors in the effects of CCPA cannot be fully ruled out, although the role of A3 receptors in the preconditioning process is far from clear, with opposite effects in different tissues [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…Cl-ENBA (number 3 in Figure 2) is a more selective A 1 AR agonist for in vivo use than 1 and 2 (Carlin et al, 2017). CGS21680 (not shown) is an A 2A AR agonist in rat, but has substantial human (h) A 3 AR affinity (Alnouri et al, 2015). Potent A 2A AR agonist ATL-313 5 attenuates colitis in mice and reduces pro-inflammatory cytokines (Longhi et al, 2017).…”
Section: Medicinal Chemistry Of Purinergic Receptorsmentioning
confidence: 99%